Digital games as tools for corporate work and movement in the learning process (Research, Society and Development, 2022)
Movement must be part of the school experience, becoming a constructive part of learning. This training process is not only linked to cognitive learning, but also to the learning of meaning and the body. Aiming to link interdisciplinarity to movement, with a view to breaking this dualistic barrier, we seek to validate games capable of perceiving the child's movements in order to generate a real-time interaction with digital dynamics that stimulate the same. In this sense, this article seeks to develop game prototypes using Scratch to assist children in learning, involving physical interaction. From this perspective, there is the insertion of the child in a playful digital environment with activities that develop the expected skills, where the movements interact with them. To support this discussion, the present work has as its theoretical foundation the Learning Based on Digital Games combined with physical exercises, the exerlearnings. The exerlearnings for this work bring the possibility of integration of movement in the area of ​​languages, ceasing to be an exclusive factor for the discipline of Physical Education. It is expected that the artifact will contribute positively to the education of children, making the concepts of the area of ​​languages ​​work and experience.